FoodBioTimerAssay: a new microbiological biosensor for detection of Escherichia coli food contamination (Italian Journal of Public Health, 2008)
Background: Prevention of foodborne diseases is a fundamental goal for public health and industries engaged in food preparation and distribution. The correct procedure to ensure an effective prevention of foodborne diseases consists essentially in microbiological monitoring and enumeration of indicator microorganisms of faecal contamination at critical control points along the food producing procedures. Here, we propose a new microbiological biosensor, called FoodBioTimerAssay (FBTA), for rapid and reliable detection of Escherichia coli as indicator of faecal contamination in food and surface samples.Methods: A total of 122 samples were analysed using both experimental FBTA and Reference method. FBTA employs FBTM medium and counts bacteria through microbial metabolism measure: the time required for colour switch (red-to-yellow) of FBTM, due to E. coli metabolism, is correlated to initial bacterial concentration.Results: FBTA results showed an overall agreement percentage with Reference method equal to 97.54%. Discrepancies concerned three samples (1 food and 2 surface samples). Moreover, the time required to perform FBTA method was 3-fold shorter than Reference one.Conclusions: FBTA method may be considered a useful tool for detection of E. coli contamination in food and surface samples. Therefore, FBTA method may be successfully employed in risk analysis of foodborne diseases.
Keywords: HACCP; FBTA; foodborne disease prevention; Escherichia coli detection